Optimal Combustion Conditions for a Small-scale Biomass Boiler - Viktor Plaček (Acta Polytechnica, 2012)
This paper reports on an attempt to achieve maximum efficiency and lowest possible emissions for a small-scale biomass boiler. This aim can be attained only by changing the control algorithm of the boiler, and in this way not raising the acquisition costs for the boiler. This paper describes the experimental facility, the problems that arose while establishing the facility, and how we have dealt with them. The focus is on discontinuities arising after periodic grate sweeping, and on finding the parameters of the PID control loops. Alongside these methods, which need a lambda probe signal for proper functionality, we inroduce another method, which is able to intercept the optimal combustion working point without the need to use a lambda sensor.